Brain-based learning: How does mathematics creativity develop in elementary school students? - Adi Apriadi Adiansha; Khairul Sani; Raden Sudarwo; Nasution Nasution; Mulyadi Mulyadi (Universitas PGRI Madiun, 2021)
The urgency that occurs in the learning process at the Bima Regency Elementary School is the difficulty of students learning how to find innovative, effective, and creative answers so that they are unable to solve problems from various points of view. This study aims to determine how the Brain-Based Learning model influences the development of mathematics creativity in elementary school students. This type of research using experimental research design true experimental design using the technique pretest-posttest control group design. The research held in elementary schools, with the sampling technique used was probability sampling theory with the cluster sampling method. Data collection techniques using test questions and data analysis techniques pretest-posttest, normality test, homogeneity test, and t-test. The results showed that the Brain-Based Learning model had an innovative impact in developing students' creativity and provided opportunities for students to express their ideas and ideas that were then validated by students and teachers. An active and conducive learning environment created evaluation took place. This research provides benefits and deserves to continue improving education quality, especially in Indonesia